Airport System Control in Conditions of Discrete Random Processes of Traffic Flow - Usenik, Janez; Radačić, Željko; Pavlin, Stanislav (Promet - Traffic&Transportation, 2012)
The article presents a system approach to air traffic operationand control. A mathematical model of the system has beendeveloped, for the case when the input/output functions are discreterandom processes. A solution for a special example of inputfunctions has been calculated and analysed.